Patterns of durational variation in British dialects - Loukina, A; Kochanski, G (2010)
We present the results of a quantitative study of durational variability in several British dialects. The study is based on the IViE corpus (Grabe 2001), which contains recordings of speakers from seven central urban dialects of English from the UK and Ireland. The corpus used in this study included speakers from Belfast, Cambridge, Newcastle, Leeds, Dublin, monolingual London residents of Jamaican decent and bilingual Bradford residents of Punjabi decent. We used reading and re-telling of "Cinderella" story by 6 female and 6 male speakers of each dialect (7 female and 5 male for London). The read version of Cinderella was split into 5 parts. The total total number of sound files used for analysis was 465. The corpus was automatically segmented into vocalic and consonantal intervals. We then computed 15 published measures of durational variability (for example, %V or VnPVI). To compare the variation between the dialects with variation within the dialects, we used classifier algorithms based on all possible combinations of 1, 2 or 3 measures (more than 2000 in total). We found that there is a substantial overlap between the dialects leading to a relatively low classification rate: based on various combinations of the rhythm measures, the classifiers could correctly identify the dialect of not more than 30% of data (chance=15%). We see an increase in performance of the classifiers based on greater number of rhythm measures. This shows that our previous finding that rhythm is a multidimensional phenomenon (Loukina et al. 2009) is true not only for different languages, but also for different dialects of the same language. Our classifiers showed higher identification rates for Belfast English. These results agree with the results previously reported by Ferragne (2004, 2008) who conducted a similar study on a different corpus of British dialects: they found that rhythm measures computed on Ulster English were different from other accents in their corpus. Contrary to their result, we find little overlap between Belfast and Dublin English. We also found better classification rates for the two 'ethnic minorities' accents: Punjabi and Jamaican The patterns we found based on measures of durational variability are partially similar to what has been reported for intonation contours. Based on the same corpus, Coleman, Grabe and Kochanski (submitted) reported significant differences between Belfast and other dialects. At the same time, duration-based measures do not show the distinction between 'Northern' and 'Southern' dialects observed by Coleman et al., but separate the two dialects spoken by 'ethnic minorities'. This suggests complex patterns of interaction between different aspects of prosodic structure.